2011
DOI: 10.1371/journal.pone.0024086
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Background Strongly Modifies the Severity of Symptoms of Hirschsprung Disease, but Not Hearing Loss in Rats Carrying Ednrbsl Mutations

Abstract: Hirschsprung disease (HSCR) is thought to result as a consequence of multiple gene interactions that modulate the ability of enteric neural crest cells to populate the developing gut. However, it remains unknown whether the single complete deletion of important HSCR-associated genes is sufficient to result in HSCR disease. In this study, we found that the null mutation of the Ednrb gene, thought indispensable for enteric neuron development, is insufficient to result in HSCR disease when bred onto a different g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 50 publications
4
44
0
Order By: Relevance
“…In a previous study, we reported that there are resistant loci to aganglionosis in the genetic background of the F344 strain [3]. Despite the decrease in the expression level of the Ednrb gene and hypoganglionosis, JF1 mice do not show any megacolon symptoms (n=150).…”
mentioning
confidence: 89%
“…In a previous study, we reported that there are resistant loci to aganglionosis in the genetic background of the F344 strain [3]. Despite the decrease in the expression level of the Ednrb gene and hypoganglionosis, JF1 mice do not show any megacolon symptoms (n=150).…”
mentioning
confidence: 89%
“…The genetic background of inbred rodents also has important effects on ENS morphogenesis and disease phenotypes (Dang et al, 2011; Walters et al, 2010). This observation suggests that in outbred human populations there may also be diverse and unpredictable responses to cell transplantation because of unknown genetic modifier effects.…”
Section: What Are the Most Appropriate Models For Experimentation mentioning
confidence: 99%
“…When bred onto two different genetic backgrounds, these features were differently modified. Among three strains of homologous rats, the AGH-mutant rats showed the most serious aganglionosis, followed by the LEH and F344 mutants, which corresponded to the order of their average survival time (5). Thus, we concluded that variations in penetrance and survival period among the three strains of Ednrb sl/sl rats were attributable to distinct differences in the severity of aganglionosis, and modifier genes in the genetic backgrounds of these strains significantly modulated the severity of the aganglionosis phenotype.…”
Section: Table 1 Peripheral White Blood Cells (Wbc) Red Blood Cells mentioning
confidence: 75%
“…We found that genetic background strongly modified the symptoms of aganglionosis but not hearing loss (5). In this study, we also investigated the impact of genet- cell counts in the mutant animals.…”
Section: Table 1 Peripheral White Blood Cells (Wbc) Red Blood Cells mentioning
confidence: 92%
See 1 more Smart Citation